Experimental Study of Inconel 718 Surface Treatment by Edge Robotic Deburring with Force Control - Burghardt, A.; Szybicki, D.; Kurc, K.; Muszyńska, M.; Mucha, J. (Проблемы прочности, 2017)
We present the results of investigations into the application of robotics for deburring and chamfering to a predefined geometric quality. The robotic application was used for a part of the manufacturing process of an aircraft engine detail. Представлены результаты исследования по оценке использования робототехники для снятия заусенец и фасок с жестким геометрическим допуском. Робототехнические средства использовались для части процесса изготовления деталей авиационных двигателей.